2018
DOI: 10.1002/mrm.27572
|View full text |Cite
|
Sign up to set email alerts
|

A method to correct background phase offset for phase‐contrast MRI in the presence of steady flow and spatial wrap‐around artifact

Abstract: Purpose Background phase offsets in phase‐contrast MRI are often corrected using polynomial regression; however, correction performance degrades when temporally invariant outliers such as steady flow or spatial wrap‐around artifact are present. We describe and validate an iterative method called automatic rejection of temporally invariant outliers (ARTO), which excludes these outliers from the fitting process. Methods The ARTO method iteratively removes pixels with large polynomial regression errors analyzed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…VNR is inversely proportional to the magnitude of Venc, hence when Cine-PC is performed to measure flow with a low velocity dynamic range (cerebrovascular blood or CSF), The prescribed Venc produces relatively high VNR in the targeted flow region [24]. In this investigation, The two different coverages demonstrated that there was no statistical difference in VNR, thus fold-over should not be selected solely for the purpose of increasing VNR value.…”
Section: Discussionmentioning
confidence: 82%
“…VNR is inversely proportional to the magnitude of Venc, hence when Cine-PC is performed to measure flow with a low velocity dynamic range (cerebrovascular blood or CSF), The prescribed Venc produces relatively high VNR in the targeted flow region [24]. In this investigation, The two different coverages demonstrated that there was no statistical difference in VNR, thus fold-over should not be selected solely for the purpose of increasing VNR value.…”
Section: Discussionmentioning
confidence: 82%
“…The comparative insensitivity of flow‐volume measurement to the amount of static tissue used for polynomial fitting shows that automated static tissue‐segmentation routines would benefit from accurate and evenly dispersed static tissue definition, whereas the omission of a large proportion of the available static tissue is acceptable, with negligible impact on measurement results. By combining this knowledge with other techniques of automated static‐tissue identification, artifact detection and weighted‐fitting algorithms, 4D‐flow MRI can be more accessible as a clinical tool …”
Section: Discussionmentioning
confidence: 99%
“…By combining this knowledge with other techniques of automated static-tissue identification, artifact detection and weighted-fitting algorithms, 4D-flow MRI can be more accessible as a clinical tool. 11,13,25 While other studies have investigated background-phase offsets in 4D-flow MRI, this is the first study to provide a comprehensive analysis of the influence of different correction techniques on vascular flow-volume measurements. Lorenz et al performed a streamline and pathline tracking analysis that showed improvement with second order, compared with linear background phase fitting in phantom experiments, but no discernable difference in in vivo tracking, F I G U R E 7 Percentage change in flow-volume measurement compared with using manually defined static tissue as a function of nonstatic tissue inclusion.…”
Section: F I G U R Ementioning
confidence: 97%
“…Prior to flow quantification, all images were corrected using a recently proposed background phase correction method 39 . Phase‐aliasing correction was performed when necessary.…”
Section: Methodsmentioning
confidence: 99%
“…Prior to flow quantification, all images were corrected using a recently proposed background phase correction method. 39 Phase-aliasing correction was performed when necessary. Net volumetric flow, peak through-plane velocity, and peak volumetric flow rate were calculated as the flow indices of interest.…”
Section: Postprocessing and Analysismentioning
confidence: 99%